Assentment of the influence of liver cirrhosis and minimal hepatic encephalopathy on quality of life - Santos, Diana (2014)
Introduction: Minimal hepatic encephalopathy (MHE) has been associated with changes in the ability to drive, with the onset of the explicit form of hepatic encephalopathy and with a worse prognosis. However, the impact of MHE on quality of life (QoL) remains controversial. With the standardization of the Psychometric Hepatic Encephalopathy Score (PHES) for the diagnosis of MHE in the Portuguese population, this study aimed to determine the effect of this neurocognitive disorder on the patients’ QoL.Methods: The sample consisted of two groups: the control group (CG, n=8) and the liver cirrhosis group (LCG, n=8). Of the eight patients in the LCG, four presented with MHE, diagnosed according to PHES criteria. QoL was assessed using the Medical Outcomes Study, Short Form 36 (SF-36).Results: Compared with the CG, the LCG had significantly lower scores in all domains of the SF-36, except for the physical pain subdomain. When patients with and without HE were compared, no significant differences were found in any of the SF-36 domains.Conclusions: Patients with liver cirrhosis have a worse QoL when compared with healthy controls; EHM does not affect QoL. Further studies with a higher number of patients are required to confirm these findings.